Involvement of bone-specific alkaline phosphatase and procollagen I carboxy-terminal propeptide as predictors of early fracture risk in Chinese children with juvenile osteoporosis: An interventional clinical trial - Wang, Yu; Zhao, Jingxin; Kong, Lingwei; Jin, Yu (Bangladesh Journal of Pharmacology, 2018)
This clinical trial was designed to understand whether the children with juvenile osteoporosis receiving tablet containing vitamin D and calcium had lower incidence of bone fracture compared to the children receiving a diet rich in calcium, vitamin D, and protein. We assessed whether plasma levels of bone-specific alkaline phosphatase (BSAP) and procollagen I carboxy-terminal propeptide levels (PIPC) could be used as predictors of early bone fracture in children. A total of 120 children of either gender with a juvenile osteoporosis were enrolled and randomized (1:1 ratio) to receive tablet containing vitamin D and calcium (n=60) or diet rich in calcium, vitamin D, and protein (n=60), and undergone follow-up for up to 3 years. Blood sample was collected and BSAP and PIPC levels were measured. The results suggested that therapeutic intervention (vitamin D and calcium) does not predict bone fracture in children. However, correlations analysis revealed that the decreased level of BSAP and PIPC were associated with higher incidence of fracture. The results suggest that the low levels of BSAP and PIPC cause increase susceptibility of fracture among children with juvenile osteoporosis.